Older Adults’ Perceptions of ICT: Main Findings from the Technology In Later Life (TILL) Study - Charles Musselwhite (Healthcare, 2019)
Technology is entwined in 21st Century society, and within the lives of people across all ages. The Technology In Later Life (TILL) study is the first piece of work contributing to the impact, behavior, and perception of technology use, by adults aged ≥70 years, residing in rural and suburban areas. TILL is an international, multi-centred, multi-methods study investigating and conceptualizing how various technologies impact the lives of older adults; residing in urban and rural locations in the United Kingdom (UK) and Canada. This in-depth study recruited 37 participants via a multi-methods approach. Analysis of the findings ascertained two overarching themes: facilitators of technology use (i.e., sharing of information and feeling secure), and detractors of technology (i.e., feelings of apprehension of use). Proposed recommendations include promotion of technology from a strengths-based perspective focusing on positive opportunities technology to improve health and wellbeing, creating a peer support network to assist with learning of new technology, and the need to examine further how intergenerational relationships may be enhanced through the use of technology. The distinction of these themes narrates to the originality of this initial study and milieu of recruited participants, intersecting across the fields of gerontology, geography, social sciences, and gerontechnolog